Legal Protection Provided by Law No. 35 of 2014 for Children Neglected by Parents Who Abuse Narcotics - Rambe, Sullama Nikmah; Lubis, Syofiaty (Universitas Islam Negeri Sumatera Utara, 2023)
Drug abuse is one of the most serious challenges in modern society, affecting not only individuals who consume drugs but also families, especially children. In Indonesia, Law No. 35/2014 on Narcotics provides a strong legal basis to protect children abandoned by parents who are drug abusers. This study aims to analyze the legal protection provided by Law No. 35/2014 to children who are victims of this situation. Law No. 35/2014 states that children have the right to protection from all forms of violence, neglect and exploitation, including in the context of parents involved in drug abuse. The law stipulates that the government is responsible for providing protection, care and rehabilitation for children affected by drug abuse, and emphasizes that parental drug abuse cannot be used as an excuse to abandon a child. In addition, Law No. 35/2014 also provides a foundation for efforts to prevent drug abuse among adolescents and children, through education and socialization about the dangers of drugs and rehabilitation for drug addicts. Nevertheless, the implementation of this legal protection still faces various challenges. Lack of awareness of children's rights and access to adequate social services are often barriers to providing effective protection for children affected by their parents' drug abuse. Therefore, greater efforts are needed from the government, non-governmental organizations, and society as a whole to improve awareness, access to services, and legal protection for children in this situation.